Potency of Bacillus cereus WPL 415 to Increase Crude Protein and Decrease Crude Fiber of Animal Feed Stuff - Lokapirnasari, Widya Paramita; Sahidu, Adriana Monica; Nurhajati, Tri; Soepranianondo, Koesnoto; Yulianto, Andreas Berny (KnE Life Sciences, 2017)
This research aims to identify isolate as a probiotic candidate derived from liquor rumen of local beef cattle and to know the ability of isolates as biofermentor on basal feed to the changes in the nutrient value. The selected samples were obtained from a slaughterhouse in Surabaya. This study consisted of two stages. The first stage was the identification of bacteria through the test of morphology, Gram staining, biochemical, resistance to acidity and 16S rDNA sequencing. The second stage was a test of the ability of the isolates on the nutrient of basal feeds by fermentation for three days in an aerobic condition. Based on the findings of the first phase, it has been identified that probiotic bacterium rods, motility positive, Gram-negative, have viability at pH 2 and pH 3 for 90 minutes and 24 hours and have the ability to ferment lactose, sucrose, galactose, ribose, cellobiose and xylose. Furthermore, based on test results of 16S rDNA sequencing, the probiotic bacterium was identified as Bacillus cereus WPL 415. Based on the research results at the second stage, Bacillus cereus WPL 415 at doses of 0.25% and 0.5% could improve the nutrient content of the basal feed. The results of the proximate analysis revealed that there was an increase in crude protein content of 6.78% until 8.12% compared to the control and was able to lower the crude fiber content of 15.19% and 17.40% compared to the control. Based on these results it can be concluded that Bacillus cereus WPL 415 from local beef cattle can be used as a probiotic candidates to improve the quality of animal feed. Keywords: Bacillus cereus, probiotic, crude protein, crude fiber